2019
DOI: 10.1186/s10086-019-1838-9
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor agent yatein from Calocedrus formosana Florin leaf induces apoptosis in non-small-cell lung cancer cells

Abstract: Calocedrus formosana Florin is a softwood tree species with high economic value in Taiwan. Several bioactivities of the extracts of C. formosana have been reported; however, only one study focused on the anti-non-small-cell lung cancer cells' (anti-NSCLC) effect of C. formosana extract and its active phytocompound. In the present study, the anti-lung cancer effects of C. formosana leaf extract and its active derivative yatein were evaluated. The results revealed that the n-hexane fraction of the crude extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Accordingly, we found that yatein treatment increased Wee1 expression in CL1-5 cells, indicating that Wee1 played a crucial role in the regulation of G 2 /M cell-cycle distribution in CL1-5 cells in the context of yatein treatment. On the other hand, we also found yatein is able to induce ROS production in A549 and CL1-5 cells in our previous study [15], suggesting that yatein may induce the oxidative DNA damage. Moreover, our previous results also revealed that the CL1-5 cells were more sensitive for the ROS production than the A549 cells after yatein treatment [15].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Accordingly, we found that yatein treatment increased Wee1 expression in CL1-5 cells, indicating that Wee1 played a crucial role in the regulation of G 2 /M cell-cycle distribution in CL1-5 cells in the context of yatein treatment. On the other hand, we also found yatein is able to induce ROS production in A549 and CL1-5 cells in our previous study [15], suggesting that yatein may induce the oxidative DNA damage. Moreover, our previous results also revealed that the CL1-5 cells were more sensitive for the ROS production than the A549 cells after yatein treatment [15].…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, we also found yatein is able to induce ROS production in A549 and CL1-5 cells in our previous study [15], suggesting that yatein may induce the oxidative DNA damage. Moreover, our previous results also revealed that the CL1-5 cells were more sensitive for the ROS production than the A549 cells after yatein treatment [15].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations